Suitability study of some surface water samples of Madhupur tract for irrigation, aquaculture and livestock consumption (Progressive Agriculture, 2015)
Surface water samples from beel, river and canal of Madhupur Tract in Bangladesh were collected and analysed to find out the suitability of those water for irrigation, aquaculture and livestock consumption. Most of the samples were alkaline in nature only two samples were found acidic (pH 4.25 and 4.00). Out of 17 samples, 11 were limiting for irrigation and 15 were unsuitable for aquaculture with respect to pH values. Electrical conductivity (EC) rated maximum samples as good category for irrigation. TDS categorized the samples as fresh water for irrigation and were suitable for livestock, drinking and aquaculture. Chloride content of a few samples were beyond recommended limit for livestock. Micronutrient concentrations were alarming for livestock and aquaculture. Cu, Mn, Fe and Zn quantities categorized all the samples unsuitable for aquaculture. Most of the samples were also unsuitable for livestock due to higher Fe and Mn contents. Ca, Na, K and P quantities of all the samples were within safe limit for irrigation, aquaculture and livestock, but Mg contents of 8 samples were above recommended limit for aquaculture. Boron level classified 4 samples as good13 as excellent for irrigation. SAR and EC combinedly rated all the samples as medium salinity and low alkalinity class (C2S1) and hardness categorized the waters in soft, moderately hard and hard water class for irrigation. Considering all parameters not a single sample was found suitable for irrigation, livestock consumption, and aquaculture.Progress. Agric. 2014. 25: 9-16